2019
DOI: 10.1001/jama.2018.20046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fecal Microbiota Transplantation on 8-Week Remission in Patients With Ulcerative Colitis

Abstract: IMPORTANCE High-intensity, aerobically prepared fecal microbiota transplantation (FMT) has demonstrated efficacy in treating active ulcerative colitis (UC). FMT protocols involving anaerobic stool processing methods may enhance microbial viability and allow efficacy with a lower treatment intensity. OBJECTIVE To assess the efficacy of a short duration of FMT therapy to induce remission in UC using anaerobically prepared stool. DESIGN, SETTING, AND PARTICIPANTS A total of 73 adults with mild to moderately activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
612
3
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 633 publications
(686 citation statements)
references
References 32 publications
11
612
3
15
Order By: Relevance
“…Although FMT seems to be a viable option for treatment of UC in future, [1][2][3][4][5] and is being propagated as "natural" therapy, its safety over short term, and more importantly over long term needs to be studied. With FMT, there are risks about unfavorable effects that donor microbiota may have on recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FMT seems to be a viable option for treatment of UC in future, [1][2][3][4][5] and is being propagated as "natural" therapy, its safety over short term, and more importantly over long term needs to be studied. With FMT, there are risks about unfavorable effects that donor microbiota may have on recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) targets gut microbiome dysbiosis and is emerging as a novel therapy for ulcerative colitis (UC). The efficacy of FMT in induction of remission in moderate-severe active UC has been addressed by four highquality randomized controlled trials [1][2][3][4] and multiple cohort studies. FMT has been shown to be effective in patients with steroiddependent UC, 5,6 and it may also have a role in long-term maintenance of remission.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the effect of microflora transplantation on recurrent CDI, the results of many studies on FMT in UC are heterogeneous [123][124][125][126][127][128][129][130][131][132] owing to the lack of a standardized process ( Table 2). 9 One study suggests that the microbial imbalance of the CDI + UC recipients is similar to that of CDI-only recipients 140 Thus, the efficacy for FMT treatment in UC is probably attributed to the occurrence of bacterial dysregulation similar to that seen in CDI.…”
Section: Effectiveness Of Fmtmentioning
confidence: 99%
“…FMT is effective for treating recurrent Clostridioides difficile infection (rCDI) (van Nood et al 2013), but is also under investigation for the treatment of ulcerative colitis (UC), Crohn's disease (CD), liver diseases, obesity and metabolic disease, food allergy, graft-versus-host disease, check point colitis and to improve the efficacy of cancer immunotherapy (Ooijevaar et al 2019;Wang et al 2018;Baruch et al 2019). Clinical trials of FMT in UC have suggested some potential for using microbiota-targeted therapy in this setting (Paramsothy et al 2017;Moayyedi et al 2015;Rossen et al 2015;Costello et al 2019), but evidence for efficacy in other indications is currently extremely limited and there is currently little or no scientific basis for the adoption of FMT as a mainstream therapeutic option outside of rCDI.…”
Section: Introductionmentioning
confidence: 99%